2019
DOI: 10.1097/nor.0000000000000513
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Discharge Readiness After Total Knee Replacement

Abstract: Total knee replacement (TKR) surgery has been found to achieve positive outcomes for many patients such as reduced pain and increased function. However, some patients experience suboptimal outcomes including falls, readmission to hospital, and reduced functional performance. Preparation for discharge after TKR surgery is often defined related to pain control, walking, knee function, and ability to climb stairs. These measures may not fully encompass aspects of recovery that impact patients' readiness for disch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 58 publications
0
18
0
Order By: Relevance
“…erefore, healthcare providers should assess patients' social support early, and their support systems should be involved in the preoperative and postoperative processes. Journal of Ophthalmology Moreover, previous studies showed that social support is an important factor that impacts readiness for discharge [15]. When patients do not have enough social support, they are less prepared for discharge from hospital.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…erefore, healthcare providers should assess patients' social support early, and their support systems should be involved in the preoperative and postoperative processes. Journal of Ophthalmology Moreover, previous studies showed that social support is an important factor that impacts readiness for discharge [15]. When patients do not have enough social support, they are less prepared for discharge from hospital.…”
Section: Discussionmentioning
confidence: 99%
“…ere may be other mediating factors making a contribution between discharge teaching and readiness for discharge such as patient characteristics and patient self-care ability [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RHD is a self-perception of patients about whether they are ready to be discharged, it is related to medical satisfaction and safety after discharge closely. Studies [7,15] have shown that the higher RHD, the stronger ability to cope with health challenges after discharge. In this study, the RHD of patients after MIE was at a medium level.…”
Section: Discussionmentioning
confidence: 99%
“…RHD is a self-perception of patients about whether they are ready to be discharged, it is related to medical satisfaction and safety after discharge closely. Studies [33,34] have shown that the higher RHD, the stronger ability to cope with health challenges after discharge. In this study, the RHD of patients after esophagectomy was at a medium level.…”
Section: Discussionmentioning
confidence: 99%